Invasive Fungal Infections in Children with Hematological Malignancy - Jamal, Chowdhury Yakub; Nigar, Ismet (Bangladesh Journal of Child Health, 2021)
Invasive fungal infections (IFI) are a major cause of morbidity and mortality in patients with haematolgical malignancies. Factors that appear to be associated with IFIs in both children and adults in this severely immunosuppressed population are the underlying malignancies, presence of profound and long lasting neutropenia, high intensity of the therapeutic regimens, hematopoietic stem cell transplantation and previous antibiotic therapy. In patients with hematological malignancy most invasive fungal infections are caused by Candida and Aspergillous species. Though the incidence of IFI in adult may be as high as 30 % and the mortality up to 50 %, the true incidence in children and its outcome are more difficult to assess because of the growing trends towards more invasive chemotherapeutic regimens, the development and introduction of new antifungal drugs and prophylactic antifungal strategies and difference in design and patient populations among the various studies. In general the incidence rate in children appears to be lower than in adults. The diagnosis are based on the basis of microbiological and radioimagings with the criteria defined by the EORTC/MSG. Caspofungin, Liposomal amphotericin B and Voriconazole are often the first line empirical antifungal agents BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 34-40